Perbedaan Efektifitas Desinfektan Amonium Kuatener 1% Dengan Fenol 1% Dalam Penurunan Angka Kuman Lantai Ruang Perawatan di RSU Kardinah Kota Tegal - Krisanti, Erlina; Nurjazuli, Nurjazuli; Suwondo, Ari (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Number of germs on the floor at the treatment room of Nusa Indah was 17 CFU/cm2 (standard of Health Minister Decree: 5-10 CFU/cm2). The room of Nusa Indah is devoted to the care of patients suffering from infectious diseases. Floor disinfectant at Kardinah Public Hospital uses phenol in accordance with the Standard Operating Procedure. The objective of this research was to analyze the effectiveness differences between quaternary ammonium and phenol disinfectants in decreasing number of germs on the floor in the treatment room at Kardinah Public Hospital in Tegal. Methode : This research used Control Time Series Design. Independent variables were quaternary ammonium 1%, phenol 1%, and contact time (minutes) during 10, 720, 1440, 2160, 2880, and 3600. Meanwhile, a dependent variable was number of germs. Study population was treatment rooms at Kardinah Public Hospital. Samples were taken by using purposive sampling. Correlation test was used to analyze the relationship between number of germs after providing either quaternary ammonium 1% and contact time or phenol 1% and contact time. On the other hand, independent T test was used to analyze differences of number of germs in the first measurement after providing quaternary ammonium 1% and phenol 1%. Result : The results ofthis research revealed that number of germs after providing quaternary ammonium 1% in the 10th minute was equal to 3 CFU/cm2, and then it rose gradually in the next minutes. In contrast, number of germs after providing phenol 1% in the 10th minute was equal to 10 CFU/cm2, and then it also gradually increased in the next minutes. Furthermore, there were any significant differences in terms of the number of germs after providing quaternary ammonium 1% and phenol 1% (p value = 0.001). Conclusion : As a conclusion, disinfectants of phenol 1% and quaternary ammonium 1% are effective to reduce number of germs in the 10th minute. The treatment room needs to use quaternary ammonium 1% because it has a greater exponential value of concentration than phenol 1%. Amonium kuatener has the smell of fresh lemon. Moreover, it is more effective to kill viruses and fungi Key Words: Quaternary Ammonium, Phenol, Floor Disinfectant, Number of Germs